Desalinating RO retentate employing NF coupled with CDI: A path towards cleaner production. (1st April 2023) - Maheshwari, Karishma; Gupta, A.B.; Gupta, Ragini; Agarwal, Madhu
Abstract: The present study proposes a strategy to treat reverse osmosis (RO) retentate via an integrated system that combines a nanofiltration module with a capacitive deionization unit. A polyamide nanofiltration (NF) membrane (HFT-200) was employed for desalting at varying pressure (3–12 kg/cm 2 ) and initial salt concentrations (500 mg/L to 3000 mg/L). It was examined that increasing the pressure resulted in an incremental upsurge in desalting performance with the strong retention of divalent ions. The permeate with most monovalent species from the NF module was fed to the channel to the capacitive deionization (CDI) unit for deionization at 1.0 V potential via Fe–Cu based bimetallic electrodes revealing strong specific capacitance of 101.19 F/g. The system was also run for treating five real RO retentate samples collected from distinct spots situated in Jaipur, Rajasthan, wherein almost 40% of divalent salt ions were effectively removed. On coupling the CDI unit, desalination of around 99% was observed. The electrosorption capacity of the electrodes was observed to be almost double than that reported in the literature on deionizing concentrated streams via biomass-derived electrodes. This paper proposes a scheme combining NF-CDI as an energy-saving and sustainable pathway to desalt massively generated RO retentate. Graphical abstract: Image 1 Highlights: An integrated system for desalting RO membrane retentate has been proposed. The sorption capacity of the electrodes was examined to be twice that of a single CDI system. The process integration of NF-CDI coupling resulted in high ion removal efficiency of up to 99%. NF-CDI hybrid process is a cost-effective system with an energy consumption of 3.5 kWh/m3. The developed NF-CDI system has shown enormous potential to treat real RO retentate.